Cardiopulmonary reserve as determined by cardiopulmonary exercise testing correlates with length of stay and predicts complications after radical cystectomy. (21st January 2015) - Tolchard, Stephen; Angell, Johanna; Pyke, Mark; Lewis, Simon; Dodds, Nicholas; Darweish, Alia; White, Paul; Gillatt, David
Abstract : Objective: To investigate whether poor preoperative cardiopulmonary reserve and comorbid state dictate high‐risk status and can predict complications in patients undergoing radical cystectomy (RC). Patients and Methods: In all, 105 consecutive patients with transitional cell carcinoma (TCC; stage T1–T3) undergoing robot‐assisted (38 patients) or open (67) RC in a single UK centre underwent preoperative cardiopulmonary exercise testing (CPET). Prospective primary outcome variables were all‐cause complications and postoperative length of stay (LOS). Binary logistic regression analysis identified potential predictive factor(s) and the predictive accuracy of CPET for all‐cause complications was examined using receiver operator characteristic (ROC) curve analysis. Correlations analysis employed Spearman's rank correlation and group comparison, the Mann–Whitney U ‐test and Fisher's exact test. Any relationships were confirmed using the Mantel–Haenszel common odds ratio estimate, Kaplan–Meier analysis and the chi‐squared test. Results: The anaerobic threshold (AT) was negatively ( r = −206, P = 0.035), and the ventilatory equivalent for carbon dioxide (VE/VCO2 ) positively ( r = 0.324, P = 0.001) correlated with complications and LOS. Logistic regression analysis identified low AT (<11 mL/kg/min), high VE/VC02 (≥33) and hypertension as significant factors, such that, in their presence patients were 5.55‐times more likely to have complications at 90 days postoperatively [ P = 0.001, 95% confidence interval (CI) 2.2–13.9]. ROC analysis showed a high significance (area under the curve 0.78, 95% CI 0.69–0.87; P < 0.001). In addition, based on CPET criteria >50% of patients presenting for RC had significant heart failure, whereas preoperatively only very few (2%) had this diagnosis. Analysis using the Mann–Whitney test showed that a VE/VCO2 ≥33 was the most significant determinant of LOS ( P = 0.004). Kaplan–Meier analysis showed that patients in this group had an additional median LOS of 4 days ( P = 0.008). Finally, patients with an American Society of Anesthesiologists grade of 3 (ASA 3) and those on long‐term β‐blocker therapy were found to be at particular risk of myocardial infarction (MI) and death after RC with odds ratios of 4.0 (95% CI 1.05–15.2; P = 0.042) and 6.3 (95% CI 1.60–24.8; P = 0.008). Conclusion: Patients with poor cardiopulmonary reserve and hypertension are at higher risk of postoperative complications and have increased LOS after RC. Heart failure is known to be a significant determinant of perioperative death and is significantly under diagnosed in this patient group.